2008
DOI: 10.1590/s0100-29452008000100037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xylella fastidiosa genetic diversity by fAFPL markers

Abstract: -The first phytopathogenic bacterium with its DNA entirely sequenced is being detected and isolated from different host plants in several geographic regions. Although it causes diseases in cultures of economic importance, such as citrus, coffee, and grapevine little is known about the genetic relationships among different strains. Actually, all strains are grouped as a single species, Xylella fastidiosa, despite colonizing different hosts, developing symptoms, and different physiological and microbiological ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
2
0
2
Order By: Relevance
“…However, the basic genetic patterns of limited genetic variability (we found only five STs) and the genetic separation of coffee and citrus isolates (see Fig. 1) were similar to the patterns observed using SNPs (47), fluorescent amplified fragment length analysis (17), and partial MLST (1).…”
Section: St11 C C C a T A C C A T G A A C -A A T T T T A T C T G T C supporting
confidence: 80%
See 2 more Smart Citations
“…However, the basic genetic patterns of limited genetic variability (we found only five STs) and the genetic separation of coffee and citrus isolates (see Fig. 1) were similar to the patterns observed using SNPs (47), fluorescent amplified fragment length analysis (17), and partial MLST (1).…”
Section: St11 C C C a T A C C A T G A A C -A A T T T T A T C T G T C supporting
confidence: 80%
“…pauca isolates, a North American plum isolate, and a North American grape isolate. However, more recently, two genomic fingerprinting studies (17,27) both showed that while PL9746 was distinct from both coffee and citrus isolates of X. fastidiosa subsp. pauca, it had a very close relationship with PLS0135 (ATCC 35871), an isolate from plum that Schaad et al (42) named as the type of the subspecies multiplex (ST41 [see reference 33]), and it had a clear separation from grape isolates (X. fastidiosa subsp.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…pauca foram realizados por meio de técnicas de RAPD, VNTR, RFLP, SSR e AFLP (Almeida et al, 2008;Kishi et al, 2008), e, mais recentemente, por análises de sequência multilocus (Parker et al, 2012) e comparação de genomas (Varani et al, 2012). Entretanto, no Brasil, a maioria dos isolados de bactérias caracterizados é obtida de pomares nos estados de São Paulo e do Paraná.…”
Section: Introductionunclassified
“…pauca (que inclui ameixa, café e citros) (SCHAAD et al, 2004;SCHUENZEL et al, 2005). No entanto, trabalhos mais recentes de variabilidade genética evidenciam separações entre isolados de hospedeiros anteriormente considerados do mesmo grupo, o que pode ser resultado da evolução de estirpes em determinadas regiões, principalmente devido à recombinação gênica (CHEN et al, 2002;WENDLAND et al, 2003;SHERALD, 2004;SCHUENZEL et al, 2005;KISHI et al, 2008).…”
Section: A Bactéria Xylella Fastidiosa Wells Et Al 1987 -Agente Causalunclassified